The effect of dietary coriander supplementation on growth performance, biochemical responses, carcass proximate composition, and heavy metal accumulation in beluga, Huso huso. Issue 1 (2nd January 2022) - Bahrekazemi, Masoumeh; Eslami, Mahboubeh; Nikbakhsh, Jaber
ABSTRACT: To determine the effect of coriander on beluga, Huso huso, a total of 150 fish (250 ± 2 g) were fed a diet containing 0, 5, 10, 15, or 20 g kg −1 of coriander for 60 days (Phase 1). The fish were then subjected to 1 mg L −1 of heavy metal exposure (lead, cadmium, and copper) for 7 days (Phase 2). The best growth performance before exposure to heavy metals was observed in beluga fed 5 or 10 g kg −1 coriander and after exposure in fish fed 10 or 15 g kg −1 coriander. While mortality occurred only in fish fed 20 g kg −1 coriander before heavy metal exposure, 100% survival was only observed for sturgeon fed 10 g kg −1 coriander after exposure. Enzyme activities and level of biochemical parameters in blood were better before heavy metal exposure in fish fed 5, 10, or 15 g kg −1 coriander, while for postexposure, fish fed 10 or 15 g kg −1 coriander showed superior biochemical responses. Carcass protein and lipid declined for all coriander treatments after exposure, but fish fed 10, or 15 g kg −1 coriander exhibited the highest levels of carcass protein and lipid in both exposure phases. Carcass ash and moisture both increased as coriander increased in diet, and levels of both proximates declined after heavy metal exposure. Furthermore, in both experimental phases, the highest and lowest amounts of cadmium, copper, and lead in carcass were measured in the control group and fish fed 15 or 20 g kg −1 coriander respectively. Based on these results, addition of 10 g kg −1 coriander to beluga diet is recommended for optimal growth and health regardless of whether rearing water is contaminated with heavy metals.